Trends and risk factors of stillbirth among women of reproductive age in Pakistan: A multivariate decomposition analysis - Shakeel, Abeera; Kamal, Asifa; Ijaz, Muhammad; Siddiqa, Maryam; Tesema, Getayeneh Antehunegn; Abushal, Tahani (Frontiers in Public Health, 2023)
Background: Every year, 2 million babies are stillborn in the world. Globally, there has been a stillbirth rate decline of about 2.0%. Even though prenatal care services have improved and new medical technology have been introduced, early stillbirths have not decreased, while late-term stillbirths have decreased slightly (6). Pakistan ranks third in South Asia for having the highest stillbirth rate. Compared to its neighbors and other developing nations, Pakistan had dismal performance in lowering maternal and neonatal fatalities. Therefore, the purpose of this study is to use a multivariate decomposition analysis to examine the patterns and factors that contributed to the change in the stillbirth rate over time. Results: Over the past five years, Pakistan's stillbirth rate has gone from 3.98% to 5.75%. According to the total multivariate decomposition analysis, the change in coefficient (change in the effect of attributes) accounted for around 81.17% of the overall change in the proportion of stillbirths, while the change in endowment was not statistically significant. The shift in the percentage of stillbirths over time was strongly influenced by changes in residency, maternal age, maternal work status, wealth status, and birth interval. Conclusion: Significant risk factors for stillbirth include sociodemographic characteristics such as rural residency, maternal age (>30), maternal work status (employed), poverty, birth interval and pregnancy-related factors. In Pakistan, biological pregnancy-related factors, such as birth spacing between two following deliveries that is longer, have also increased the incidence of stillbirth. For a safe birth, it is crucial to take care of the mother's nutrition during pregnancy. By offering free diagnostics for early detection, giving intense treatment in such circumstances, and referring these cases to gynecologists, the risk of stillbirth can be reduced.